THE URGENCY OF RESTITUTION PROVISION FOR CHILD VICTIM OF CRIME BASED ON LAW NO. 39 OF 1999 ON HUMAN RIGHTS - Putra, Aditya Dwi; Darwis, Nurlely; Sudarto (Neolectura, 2024)
Children are God's mandate that needs to be cared for, raised and trained according to their potential. A more religious view that children are entrusted, not only biological descendants that exist but their survival must be maintained, because in fact children have basic rights that have been protected by the State that must be implemented by all parties, both by and the family itself . Before the emergence of various platforms or social media, almost all crimes were committed in an offline way, where both the victim and the perpetrator faced each other directly. However, after the emergence of these various social media, where the perpetrator and the victim can be connected at a very distance at one time, many perpetrators use this media to find new victims in various ways, many children as users of these social media become victims. And often, many basic rights of child victims are missed in all legal processes, both from the reporting process, examination to case closing. This is also due to the many problems from the internal law enforcement institutions, human resources of the apparatus, to the too complicated bureaucracy determined by the state even though the majority of child victims are the children of parents who still do not understand the complicated crime process in this country. So that currently the law enforcement process through criminal justice should not only focus on providing criminal sanctions against perpetrators with a multi-level bureaucracy that must also be fulfilled by the victim to be processed, but must also accommodate the interests of the rights of child victims , one of which is through the provision of compensation, namely restitution which must actually be carried out in any aspect, because in the view of the law, Restitution should be a human right that is inherent to the child who is a victim because they actually have protection based on many laws and regulations made by the Indonesian government.